The Effect of Training and Motivation on Performance in the Moderation of Team Cooperation of Bank Indonesia Representative Office in North Sumatra Province - Azhari; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2024)
This research aims to change the organization's bad habits and make improvements to cover its shortcomings, and to determine the influence of training and motivation on performance in teamwork moderation at the Bank Indonesia Representative Office, North Sumatra Province. Every company really needs an organization that is useful for meeting human needs. The general goal of a company is to realize quality production results and maintain the survival of a company. In an effort to achieve these goals, the main driving factor is humans. Human Resources (HR) is one of the main factors for the survival of a company. The results of this research are as follows: Training has an effect on performance moderated by teamwork, getting positive results but not significant with a sample value of 0.072 and a p value of 0.229. Motivation's influence on performance is moderated by teamwork with an original sample value of -0.140 and a p value of 0.129. Teamwork has a positive and significant effect on performance with an original sample value of 0.310 and a p value of 0.006. Motivation has a positive and significant effect on performance with an original sample value of 0.462 and a p value of 0.000. Training has a positive and insignificant effect on performance with the original sample 0.157 and p value 0.116.